Front Cover: Assembling Two‐Phase Enzymatic Cascade Pathways in Pickering Emulsion (ChemCatChem 7/2019). Issue 7 (7th April 2019) - Pan, Yongchun; Qiu, Wu; Li, Qin; Zhu, Shuihong; Lin, Changxu; Zeng, Wenbin; Xiong, Xueqing; Liu, Xiang Yang; Lin, Youhui
Abstract : The Front Cover shows a one‐pot biphasic enzymatic cascade pathway with the aid of Pickering emulsion. In their Communication, Y. Pan et al. described a Pickering emulsion system with highly enhanced catalytic performance by employing hemoglobin‐coated SiO2 as robust and recyclable Pickering interfacial biocatalysts. Besides, this biphasic system was introduced for biomolecular logic‐based computing based on multienzyme reactions. More information can be found in the Communication by Y. Pan et al. onpage 1879 in Issue 7, 2019 (DOI:10.1002/cctc.201900098 ).